2013
DOI: 10.4236/snl.2013.33009
|View full text |Cite
|
Sign up to set email alerts
|

Changing of Defect’s Structure and Properties of Superhard Nanostructured Ti-Si-N Coatings, Fabricated Using CPVD, before and after Annealing

Abstract: Using such unique methods of analysis as slow positron beam (SPB), RBS, µ-PIXE (proton microbeam), XRD, SEM with EDS, XPS, nanohardness and elastic modulus measurements, we studied superhard nanostructure Ti-Si-N coatings, which were deposited using Cathodic-PVD method, before and after annealing at the temperature of 600˚C for 30 minutes. It is shown in the paper that redistribution of N and Si occurs on the borders of nanograins after annealing, amorphous phase α-SiN x (Si 3 N 4 ) is created, defects segrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…This is consistent with the Hall-Petch relation, from which it follows that reducing the grain size to a certain critical value leads to an increase in the hardness and strength of the nitride compound [4]. At silicon concentrations of 6-8 at.%, the TiZrN coating has a nanocomposite structure characterised by the formation of an amorphous tissue Si3N4 [5][6][7][8]. Coatings with…”
Section: Introductionsupporting
confidence: 77%
“…This is consistent with the Hall-Petch relation, from which it follows that reducing the grain size to a certain critical value leads to an increase in the hardness and strength of the nitride compound [4]. At silicon concentrations of 6-8 at.%, the TiZrN coating has a nanocomposite structure characterised by the formation of an amorphous tissue Si3N4 [5][6][7][8]. Coatings with…”
Section: Introductionsupporting
confidence: 77%
“…In this way, the metallic components covered with ceramic coatings can provide both the inertness of ceramics and the tensile strength of metallic alloys, minimizing the release of heavy metal ions and wear particles. Ceramic coatings, such as titanium oxides (TiO 2 [5]), titanium and silicon nitrides (TiN [6,7], SiN [8], TiSiN [9,10]), and titanium oxynitrides (TiON [6]) proved good biocompatibility and biomechanical properties, being proper for load bearing applications, such as knee and hip joints. Moreover, previous studies demonstrated that the addition of some amount of Si into the nitrides could improve their mechanical and tribological characteristics [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…All the above methods of the treatment and deposition of protective coatings have their advan tages and disadvantages, as it follows from the analysis of publications [10][11][12][13][14]. One of the promising lines in producing protective coatings is the deposition from plasma obtained by vacuum-arc cathodic evaporation [4,[15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%